Автентифікації та безпека ІоТ-пристроїв у контексті архітектури нульової довіри - Нєдєльніцев, І. В. (ХНУРЕ, 2025)
Integrating the principles of Zero Trust Architecture (ZTA) with Internet of Things (IoT) devices can greatly improve security, but also poses challenges related to user experience, development costs, and device capabilities. This article highlights the use of geolocation and biometric authentication factors, caching authentication data, leveraging existing security libraries, and moving heavy computing operations to cloud services. Together, these approaches improve ZTA for the IoT without unduly compromising usability or incurring excessive costs.
Keywords: ІоТ пристрій; біометрична автентифікація